2018
DOI: 10.4054/demres.2018.38.24
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of US teen childbearing and smoking risk

Abstract: BACKGROUND Teenage motherhood and smoking have important health implications for youth in the United States and globally, but the link between teen childbearing and subsequent smoking is inadequately understood. The selection of disadvantaged young women into early childbearing and smoking may explain higher smoking levels among teen mothers, but teen motherhood may also shape subsequent smoking through compromised maternal depression or socioeconomic status, and race/ethnicity may condition these processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Infant welfare also related with their mother life style, such as smoking, alcoholic, body exercise, and level of nutrition their consumed. The smoker teen mother who are reducing smoking during pregnancy, can improve teen, maternal, and infant health status, in the US health status increase and longevity (Sloan and Wang, 2008;Mollborn, Woo and Rogers, 2019). Moreover, Kodzi and Kravdal (2019) found that increasing parity on having a child with low birth weight at normative range, but the high parities have the lower chance of low birth weight than the low parities.…”
Section: Pkh As Part Of Social Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Infant welfare also related with their mother life style, such as smoking, alcoholic, body exercise, and level of nutrition their consumed. The smoker teen mother who are reducing smoking during pregnancy, can improve teen, maternal, and infant health status, in the US health status increase and longevity (Sloan and Wang, 2008;Mollborn, Woo and Rogers, 2019). Moreover, Kodzi and Kravdal (2019) found that increasing parity on having a child with low birth weight at normative range, but the high parities have the lower chance of low birth weight than the low parities.…”
Section: Pkh As Part Of Social Protectionmentioning
confidence: 99%
“…Those programs will have strong impact for future generation if the government invests their money to protect the vulnerable groups especially infant and low income pregnant mother. Therefore, the infant welfare is related with families' background such as income, education, life style, and health awareness (physical and mental) (Sparrow, 2006; The National Team for Acceleration of Poverty Reduction, 2014; Kodzi and Kravdal, 2019;Mollborn, Woo and Rogers, 2019).…”
Section: Pkh As Part Of Social Protectionmentioning
confidence: 99%